Missio Dei and Religious Tolerance in Nigeria: A Historical Perspective - Bassey Owai Obio (dialektika kontemporer, 2026)
Missio Dei is a concept in the theology of mission that was formalized in the twentieth century by the International Missionary Council in 1952. It was used to reorganize mission understanding from a human or church centered mission to a God centered mission. As a result, the focus of Christian mission was redirected to the Trinitarian nature of the sending God. This paper explores the historical understanding and application of this concept of Missio Dei in the Nigerian context. It argues that proper understanding and application of Missio Dei can enhance religious tolerance in the face of persistent religious conflicts in Nigeria. The paper employs a historical theological approach in which historical data combines with theological interpretations to determine results. It uses library studies and internet sources to gather data. The paper shows how Missio Dei can reduce religious tension and enhance peaceful coexistence in a pluralist society like Nigeria. It brings this concept into the Nigerian local context through a phrase called akara ofuri ererimbot, which is a Nigerian language meaning